Enhancing the serviceability of IMS-based multimedia services: preventing core service failures. (11th March 2009) - Boucadair, M.; Morand, P.; Borges, I.; Tomsu, M.
The delivery of highly available and robust service offerings is a critical objective for Service Providers. Despite current deployment of IMS-based architectures assumes a vertical integration, IMS-based services can be offered without having a control on the underlying IP network. This paper introduces a solution to enhance the robustness of IMS-based architectures without assuming a vertically integrated system. The paper focuses on failures experienced by core service nodes and describes an autonomic solution to allow customers access to the service during failures.